Moving methodologies: doing practical and missional theology in an African context - Cilliers, Johan (Stellenbosch teologiese refleksie, 2022)
"The focus of Moving methodologies falls on Practical Theology and Missiology – and their methodologies. These methodologies have been on the move within African settings, particularly during the past few decades. This book represents an effort to map some of these movements." --